Examing the finance growth nexus in the four asian tigers - Christine Silenie, Babu (Universiti Malaysia Sarawak, (UNIMAS), 2015)
A large theoretical and empirical literature has focused on the impact of financial deepening on the economic growth throughout the world. Financial deepening is the increased provision of financial services with a wider choice of services available to the society. It also reflects the macro effects of financial deepening on the larger economy. This study aims to investigate the finance growth nexus and its impact in the Four Asian Tigers which comprises of Singapore, Hong Kong, South Korea and Taiwan. This will be done using a dataset from these four countries for the period 1998 – 2014. As is done from various similar studies, the results suggest beneficial effect of financial deepening on economic growth and further analysis resulted in differences which may have come from underlying factors such as regulations and government interventions with its ability to provide widespread access to financial services. Thus, this study aims to identify and investigate the existence of finance growth nexus in the Four Asian Tigers and its implications on its economy.